PENGARUH BIAYA LINGKUNGAN, KINERJA LINGKUNGAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (STUDI KASUS MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019-2023) - Saniah Saniah; Rohma Septiawati; Fista Apriani Sujaya (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study analyzes the effect of environmental costs, environmental performance, and company characteristics on corporate social responsibility (CSR). Environmental costs reflect a company's efforts in disclosing environmental effects on financial statements, while environmental performance measures the extent to which a company implements environmentally friendly policies. In addition, firm characteristics, such as size and industry sector, are thought to influence the level of firm involvement in CSR activities. To examine how these variables interact with each other, this study uses a quantitative approach, including regression analysis. The data used comes from the annual reports of companies listed on the Indonesian stock exchange, as well as sustainability reports published within a certain period. The results show that environmental performance and firm characteristics have a positive and significant impact on CSR, while environmental costs have varying impacts depending on the indicators used. The findings confirm the importance of environmental transparency and accountability in enhancing corporate engagement in CSR. The implications are expected that this study will provide insights on corporate management, investors, and regulators in encouraging more sustainable business practices.